TYPES OF ONLINE LEARNING PLATFORMS - Dilbar Primova (Лучшие интеллектуальные исследования, 2023)
Annotation: Interactive e-learning as the word interactive implies allows for active communication between students and teachers .It is a popular form of e-learning because of the free flow of information .Interactive e-learning encourages timely adjustment to teaching materials or learning expectations to support successful learning